Shigella Infection in a SCID Mouse-Human Intestinal Xenograft Model: Role for Neutrophils in Containing Bacterial Dissemination in Human Intestine - Zhang, Zhi (American Society for Microbiology, 2001)
Shigellae infect human intestine and cause intense inflammation and destruction of colonic and rectal mucosa. To model the interactions of shigella with human intestine in vivo, we have studied shigella infection in human intestinal xenografts in severe combined immunodeficient mice (SCID-HU-INT mice). Inoculation of shigella into human intestinal xenografts caused severe inflammation and mucosal damage, which was apparent as soon as 4 h following infection. Shigella infection was associated with human intestinal production of interleukin-1B (IL-1B) and IL-8 and a marked neutrophil influx into the graft. Depletion of neutrophils from SCID-HU-INT mice reduced inflammation in the human intestinal xenograft in response to shigella infection but failed to significantly alter tissue damage. However, the number of intracellular bacteria was more than 20-fold higher in the human intestinal xenografts from neutrophil-depleted SCID-HU-INT mice. Infection of human intestinal xenografts with an attenuated vaccine strain of shigella (CVD1203) induced lower levels of IL-1B and IL-8 than wild-type shigella and caused only moderate damage to the intestinal permeability barrier. Our studies establish the SCID-HU-INT mouse as a viable model for studying the interactions between shigella and human intestine and indicate that neutrophils are important for controlling the invasion of human intestine by shigella.